2021
DOI: 10.2147/ahmt.s292110
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Profile in Jimma University Medical Center, Southwest Ethiopia

Abstract: Background: Sexual assault cases are increasingly reported in Ethiopia and worldwide. However, in Ethiopia, sexual assaults' profile was not investigated well, regardless of its social, physical, and psychological impacts on survivors. Hence, this study assessed the survivors' characteristics, circumstances of the victims, and treatment offered with the view of describing the management process, and service responsiveness. Methods: A descriptive study with 3 years retrospective chart review was conducted in Ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…19 In Ethiopia, homosexuality is forbidden by law. 16 However, in this study 4.4% of the survivors were males. This is similar to other studies at Saint Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia (4.3%), 3 and Jimma University Medical Center (4%).…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…19 In Ethiopia, homosexuality is forbidden by law. 16 However, in this study 4.4% of the survivors were males. This is similar to other studies at Saint Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia (4.3%), 3 and Jimma University Medical Center (4%).…”
Section: Discussioncontrasting
confidence: 61%
“… 3 Another study conducted in Jima, Ethiopia, showed that 20.9% and 50% of study participants presented to the hospital within 72 h and after 5 days, respectively. 16 The delayed presentation is because of the high percentage of children and teenagers (88.1%) in the current study who might not report until the parents notice the condition. It can also be explained by the fear and embarrassment that they envisaged.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations